PEMBANGUNAN KAWASAN INDUSTRI BULUMINUNG OLEH BADAN PERENCANAAN, PENELITIAN DAN PENGEMBANGAN KABUPATEN PENAJAM PASER UTARA - Sahril Syamsul; Heryono Susilo Utomo; Santi Rande (Program Studi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
The development of industrial estates can encourage the growth of the industrial sector to be more targeted, integrated and provide outcomes that can stimulate economic growth and increase regional income. The purpose of this study is to describe and analyse the development of the Buluminung Industrial Area by the Planning, Research and Development Agency of Penajam Paser Utara Regency and to identify the inhibiting factors. The development of the Buluminung Industrial Area in this study is seen from the preparation stage which includes location selection, analysis of multiple effects and preparation of documents, as well as inhibiting factors. The result of this study indicate that the development of the Buluminung Industrial Area by the Planning, Research and Development Agency of Penajam Paser Utara Regency is appropriate because its strategic position and has the potential for local raw materials supported by adequate facilities and infrastructure. However, to become an industrial area, there are still many things that need to be prepared by the local government. The appointment of part of the administrative area of Penajam Paser Utara Regency to become the capital of the country is a factor inhibiting efforts to develop the Buluminung Industrial Area because it affects spatial plan, beside making the government less focused.